The meaning of the flora and fauna motifs on Malay traditional cannons - Hasanuddin Yusof,; Zuliskandar Ramli,; Muhammad Uzair Ismail,; Mohd Samsudin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The use of ornaments and motifs on cultural objects, such as houses, boats and weapons is a must in the Malay culture. While the main purpose of ornamentation is to beautify an object through aesthetics, the motifs used also contains specific connotations and philosophy. Accordingly, the ornaments are also present on traditional Malay cannons. Interestingly, these ornaments are similar with the ones used to beautify homes, mosques, vessels, textiles and so on. This study uses methods in the field of fine art by way of achieving images of cannon motifs through sketching techniques. Analysis was performed on each motif obtained from the field study in which each motif was photographed and sketched using Adobe Illustrator software. Among the motifs used in the ornaments of the cannon consists of flora and fauna motif, such as pucuk rebung, bunga teratai, tampok manggis, naga, kuda laut and ikan lumba-lumba to name a few. Therefore, each particular motif used to beautify the cannons has an intrinsic meaning that corresponds to the goal of the gunners. For instance, the pucuk rebung symbolizes patience, tampok manggis symbolizes politeness and good manner, while kuda laut and ikan lumba-lumba symbolizes persistence, steadfastness, agility, intelligence and so forth. Hence, the use of these motif were not simply aesthetics, but as a form of communication between the engraver with the user of the cannon, in which the motif or symbols carries valuable messages which also serves as a form of guidance, motivation or advice in the battlefield.